Book one : shipwreck : island - Korman, Gordon (New York : Scholastic Inc., 2001)
Book one: shipwreck Island Luke, J. J., Will, Lyssa, Charla, and Ian. They didn't want to be on boat in the first place. they didn't want to bo stuck at sea with a bunch of strangers. But when you're in the middle of the Pacific Ocean, there's no easy way ait. And when a terrifying storm hits, there's no way to fully prepare. It's all about survival.
Libro uno: naufragio Isla Luke, J. J., Will, Lyssa, Charla e Ian. No querían estar en el barco en primer lugar. no querían que Bo estuviera atrapado en el mar con un grupo de desconocidos. Pero cuando estás en medio del Océano Pacífico, no hay una manera fácil de hacerlo. Y cuando una tormenta aterradora golpea, no hay manera de prepararse completamente. Es todo sobre la supervivencia.
Keywords: NORTH AMERICAN LITERATURE -- SHORT STORIES; LITERATURA NORTEAMERICANA -- HISTORIAS CORTAS